Предмет: Алгебра, автор: poii14

Срочно! Упростить выражение ​

Приложения:

Ответы

Автор ответа: nafanya2014
0

(\sqrt[4]{m}+\sqrt[4]{n})^2=\sqrt{m}+\sqrt[4]{mn}+\sqrt{n}\\ \\(\sqrt[4]{m}-\sqrt[4]{n})^2=\sqrt{m}-\sqrt[4]{mn}+\sqrt{n}\\ \\ (\sqrt[4]{m}+\sqrt[4]{n})^2+(\sqrt[4]{m}-\sqrt[4]{n})^2=\sqrt{m}+\sqrt[4]{mn}+\sqrt{n}+\sqrt{m}-\sqrt[4]{mn}+\sqrt{n}=2\sqrt{m}+2\sqrt{n}

m-n=(\sqrt{m}-\sqrt{n})(\sqrt{m}+\sqrt{n} )

\sqrt{m^3}-\sqrt{n^3}=(\sqrt{m})^3-(\sqrt{n})^3 =(\sqrt{m}-\sqrt{n})((\sqrt{m})^2+\sqrt{m}\sqrt{n}+(\sqrt{n})^2)=(\sqrt{m}-\sqrt{n})(m-\sqrt{mn}+n)

Итак

\frac{(\sqrt[4]{m}+\sqrt[4]{n})^2+(\sqrt[4]{m}-\sqrt[4]{n})^2}{2(m-n)}:\frac{1}{\sqrt{m^3}-\sqrt{n^3}}-3\sqrt{mn}=\\ \\=\frac{2(\sqrt{m}+\sqrt{n)}}{2(\sqrt{m}-\sqrt{n)}(\sqrt{m}+\sqrt{n})}\cdot\frac{(\sqrt{m}-\sqrt{n})(m+\sqrt{mn}+n)}{1}-3\sqrt{mn}= m-2\sqrt{mn}+n=\\\\=(\sqrt{m}-\sqrt{n})^2

Похожие вопросы
Предмет: Математика, автор: k253488